2011
DOI: 10.1167/iovs.11-7647
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Posterior Surface to the Corneal Aberrations in Eyes after Keratoplasty

Abstract: Posterior surfaces compensate for anterior aberrations in normal, PK, and DALK eyes. In DSAEK eyes, the posterior surface increased total corneal HOAs and had a negative influence on MTFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 24 publications
4
67
1
1
Order By: Relevance
“…Theories include a more regular posterior graft surface with greater thickness uniformity , 31,77,112 thinner grafts with a better match in curvature, and improved parallelism between the graft and recipient and improved optical compensation by the posterior cornea. 139 Posterior corneal HOAs are increased after all forms of EK compared with normal controls, 21,54,84,108,137 and posterior corneal HOAs after DSAEK seem to be comparable to or greater than post-PKP. 21,108 It has been suggested that the posterior corneal surface is the source of increased whole-eye HOAs after DSEK compared with normal eyes or eyes post-PKP.…”
Section: Influence Of the Posterior Cornea (Donor Graft)mentioning
confidence: 88%
See 4 more Smart Citations
“…Theories include a more regular posterior graft surface with greater thickness uniformity , 31,77,112 thinner grafts with a better match in curvature, and improved parallelism between the graft and recipient and improved optical compensation by the posterior cornea. 139 Posterior corneal HOAs are increased after all forms of EK compared with normal controls, 21,54,84,108,137 and posterior corneal HOAs after DSAEK seem to be comparable to or greater than post-PKP. 21,108 It has been suggested that the posterior corneal surface is the source of increased whole-eye HOAs after DSEK compared with normal eyes or eyes post-PKP.…”
Section: Influence Of the Posterior Cornea (Donor Graft)mentioning
confidence: 88%
“…This has led some authors to reason that changes in the posterior cornea should not affect visual acuity. 54,138 Although correlation has been demonstrated between anterior corneal HOAs and postoperative BCVA, 84,108,137,139 several studies have failed to find a similar association between posterior corneal HOAs and postoperative BCVA. 68,81,84,133,137 Despite this, the impact of the posterior corneal surface on visual outcomes should not be ignored.…”
Section: Influence Of the Posterior Cornea (Donor Graft)mentioning
confidence: 99%
See 3 more Smart Citations